The Role of Lifestyle In Mediating The Influence of Financial Literacy And Financial Inclusion on The Financial Behavior of PT PNM Employees - Faisal, Faisal; Hedwigis Esti Riwayati (Cita konsultindo, 2025)
This study aims to examine the influence of financial literacy and financial inclusion on employees' financial behavior, as well as to test the role of lifestyle as a mediating variable in these relationships. The research was conducted on employees of PT Permodalan Nasional Madani Aceh Branch using a quantitative approach with a survey method involving 100 respondents. Data analysis was carried out using Structural Equation Modeling–Partial Least Square to test the direct and mediating relationships between variables. The findings reveal that financial literacy influences financial behavior, and financial inclusion also influences financial behavior. However, financial literacy does not affect lifestyle, while financial inclusion influences lifestyle. Lifestyle significantly affects financial behavior. Nevertheless, this study shows that lifestyle cannot mediate the relationship between financial literacy and financial behavior, nor between financial inclusion and financial behavior. These results emphasize the importance of financial literacy and financial inclusion in shaping positive financial behavior, with lifestyle serving as a significant direct supporting factor but not as a mediator. Efforts to enhance financial literacy and improve access to financial inclusion can serve as key strategies for improving employees' financial behavior.